Molecular typing of Aeromonas species using RAPD and ERIC-PCR fingerprinting - Abdulhadi, Yousr Noaman; Napis, Suhaimi; Rahmat Ali, Gulam Rusul; Mohamed Alitheen, Noorjahan Banu; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Two molecular typing methods were used in this study to examine the intra/inter-specific genetic relatedness among the A. hydrophila, A. caviae and A. veronii biovar sobria strains. In the analysis by RAPDPCR and ERIC-PCR, the size for RAPD and ERIC fragments ranged from 0.25 to 10.0 kb with an average number of sixteen and eight bands, respectively. For the inter-species similarity, RAPD could generate 16 major clusters and 36 single isolates at the similarity of 30%. 10 clusters are significant since it grouped the strains according to their own species, however, ERIC-PCR could discriminate the strains into 4 significant clusters and 64 single isolates at the similarity of 50%. Moreover, there was no genetic similarity between food and environmental strains of Aeromonas sp. isolated from different geographical areas as well as from the same geographical area. Eighty five genotypes among the 85 A. hydrophila, A. caviae and A. veronii biovar sobria isolates were generated using RAPD and ERIC-PCR which indicated that the strains were very diverse.